A battle of values: analysing the changing attitudes towards African refugees in Europe - Mannion, Megan Kate (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
Cosmopolitanism is a moral perspective that stresses the importance that every human being is an equal and ultimate unit of moral concern. These principles make cosmopolitanism more concerned for and accommodative towards outsiders to a political community. Against the abstraction and universalism of cosmopolitanism, communitarianism emphasizes the role communities play in shaping our individual identities and sees it as justified that the interests and well-being of community members receive priority over those of outsiders. Both these value systems are present in Europe. The question is about which direction the trend has moved in recent decades. This dissertation examines the changing values that inform attitudes toward African refugees in Europe to get at this issue. Have attitudes towards African refugees shifted in a cosmopolitan or a communitarian direction in recent decades? This dissertation examines newspaper articles from The Guardian between 1990 and 2022 to track changes in value. The analysis of these articles uncovered that communitarian values were the most prevalent and stayed the most prevalent from 1990 to 2022. These findings indicate that communitarian values are higher than cosmopolitan values regarding African refugees within the general European context. These findings add to the growing body of knowledge regarding attitude shifts, and they provide a timeline for value changes that can help predict future values and be used in future comparative studies.
Keywords: Refugees -- Africa; Refugees -- Public opinion -- Europe; Cosmopolitanism; Communitarianism; Racism against Black people; Xenophobia in mass media